Computer and Information Ethics - Bill T. Johnson (Issues in Science and Technology Librarianship)
This article reviews the book Computer and Information Ethics. Series: Contributions to the Study of Computer Science, #4, G.E. Gorman (Advisory Editor). Westport, Connecticut: Greenwood Press, 1997, by John Weckert and Douglas Adeney.